Determination of Threshold Electric Field<tex>$rm E _rm C$</tex>of Soil Under High Impulse Currents - Nor, N.M.; Haddad, A.; Griffiths, H. (2005)
A threshold electric-field intensity (E-c), above which soil ionization occurs, has been known to be important to predict soil behavior under high impulse currents. However, published results [1]-[5] reveal a wide range of values of E-c (1.3 to 20 kV/cm) and the effects of many other factors such as soil resistivity, impulse polarity, and electrode geometry require further investigation. The aim of this investigation was to quantify the effects of soil resistivity, the impulse polarity on the threshold electric field (E-c) of soil under fast transients.